Herbal Medicines for Asthmatic Inflammation: From Basic Researches to Clinical Applications - Fang Liu; Nan-Xia Xuan; Song-Min Ying; Wen Li; Zhi-Hua Chen; Hua-Hao Shen (Hindawi Limited, 2016)
Asthma is one of the most common chronic inflammatory disorders, associated with reversible airflow obstruction, airway hyperresponsiveness, and airway remodeling. This disease has a significant impact on individuals, their families, and society. Standardized therapeutics such as inhaled corticosteroid in combination with long acting β2 agonist have been applied for asthma control; however, complementary and alternative medicines, especially herbal medicines, are still widely used all over the world. A growing body of literature suggests that various herbals or related products might be effective in inhibiting asthmatic inflammation. In this review, we summarize recent advances about the mechanistic studies of herbal medicines on allergic airway inflammation in animal models and their potential application into clinic for asthma control.